2017
DOI: 10.1002/eco.1855
|View full text |Cite
|
Sign up to set email alerts
|

Organic sediment pulses impact rivers across multiple levels of ecological organization

Abstract: Sedimentation is a pervasive environmental pressure affecting rivers globally. Headwaters draining catchments rich in organic soils (i.e., peat) are particularly vulnerable to enhanced sedimentation caused by land management and environmental change, yet many of the ecological consequences of peat deposition are poorly understood. We conducted a before‐after‐control‐impact experiment in two rivers draining blanket peatland in Northern England to test the effect of sediment inputs on water quality, macroinverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 57 publications
(135 reference statements)
1
33
0
Order By: Relevance
“…Nitrogen dynamics have long been considered to be influenced heavily by sediment influx in peatland catchments, with Crisp () suggesting 80% of nitrogen output in an upland headwater river was a consequence of peat erosion, and Daniels et al () showed that NH 4 released from eroded peat was nitrified rapidly. These nutrient subsidies might drive alterations to river metabolic processes in otherwise low‐productivity peatland river systems (Aspray et al, ). This points towards a need for more peatland river studies to understand the nature of interacting multiple stressors, in a manner similar to experimental manipulations that have uncovered biodiversity responses to sediment interactions with nutrients, flow and temperature alterations in lowland agricultural settings (Matthaei, Piggott, & Townsend, ; Piggott et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nitrogen dynamics have long been considered to be influenced heavily by sediment influx in peatland catchments, with Crisp () suggesting 80% of nitrogen output in an upland headwater river was a consequence of peat erosion, and Daniels et al () showed that NH 4 released from eroded peat was nitrified rapidly. These nutrient subsidies might drive alterations to river metabolic processes in otherwise low‐productivity peatland river systems (Aspray et al, ). This points towards a need for more peatland river studies to understand the nature of interacting multiple stressors, in a manner similar to experimental manipulations that have uncovered biodiversity responses to sediment interactions with nutrients, flow and temperature alterations in lowland agricultural settings (Matthaei, Piggott, & Townsend, ; Piggott et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study illustrates that more complete understanding of the mechanistic basis of invertebrate biodiversity responses to organic sedimentation requires refinement of trait databases, similar to studies focused primarily on inorganic sediments (Wilkes et al, ). While we focused on invertebrate communities in our experimental study spanning week‐ to month‐long sediment deposition events, previous work in the UK uplands showed that even short‐term (1–2 day) pulses of sediment cause effects throughout the whole aquatic ecosystem, including water quality, invertebrate drift, invertebrate community structure and ecosystem metabolism (Aspray et al, ). Such pulses are likely to occur particularly with rainfall after summer desiccation events and after needle ice weathering in winter/spring (Li et al, ; Li, Holden, & Grayson, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chironomidae [Robinson et al, 2004b] Durance & Ormerod, 2007;Gillespie et al, 2015a;White et al, 2017). These upland systems are characterized by relatively low pH, flashy flows, and low productivity (Ramchunder et al, 2009;Aspray et al, 2017); thus, biological communities are necessarily adapted to these conditions. Combined with the fact that flow releases greater than those experienced due to reservoir overspill could not be achieved, these factors can explain the minor response in macroinvertebrates.…”
Section: Benthic Macroinvertebrate Response To Flow Experimentsmentioning
confidence: 99%